Sperm recovery from urine in men with retrograde ejaculation - Álvarez Ernesto Veiga; García Nuria Zopeque; Gutiérrez Romero Javier M.; Díaz-Fierros Pilar Reimundo; Lozano Arana María D.; Pérez Tamara Rodríguez; Álvarez Javier Sánchez; Rodríguez Guadalupe Bueno; Bernardo Vanesa Castañón; Moyano Gallego María J. (Advances in Laboratory Medicine)
Retrograde ejaculation (RE) consists of the reflux backwards, towards the bladder, of the ejaculate, during the emission phase of ejaculation, causing a total or partial absence of sperm emission, with the consequent diversion of semen into the bladder during the emission phase of ejaculation. Evaluating the ejaculate may not be sufficient for identifying RE in some patients. Hence, the management of infertility may involve the use of invasive methods such as epididymal fluid retrieval or testicular biopsy.